Comprehensive analysis of lipid metabolic signatures identified CEBPD promotes breast cancer cell proliferation - Yu Zhao; Huan He; Linyan Huang; Linna Yu (Scientific Reports)
Abstract Breast cancer (BRCA) remains the leading cause of cancer-related mortality worldwide, with lipid metabolism emerging as a critical factor in tumor progression that influences cell proliferation, migration, and immune response. Insights into lipid metabolism signatures and associated genes may offer new prognostic and therapeutic avenues. In this study, we leveraged scRNA-seq and bulk transcriptome data to assess the expression patterns and prognostic significance of lipid metabolism-related genes in BRCA. Through single-cell transcriptomic analysis of primary BRCA samples, we identified a specific set of lipid metabolism signature genes and constructed a prognostic risk model based on these signatures. This model enables patient stratification by risk scores, supporting an integrated analysis of lipid metabolism, immune landscape, and clinical outcomes. Importantly, we identified CEBPD, ABCA1, and CYP27A1 as independent prognostic genes linked to lipid metabolism, with functional assays revealing an inhibitory role for CEBPD in BRCA cell proliferation. Our findings underscore the influence of adipocytes in BRCA progression and propose CEBPD as a potential target for therapeutic intervention. This study provides a foundation for further exploration of metabolism-based strategies to enhance BRCA outcomes.